Applying molecular genetics to underutilised species – problems and opportunities - Sean Mayes,; Ho, Wai Kuan; Presidor Kendabie,; Chai, Hui Hui; Siise Aliyu,; Aryo Feldman,; Razlin Azman Halimi,; Festo Massawe,; Sayed Azam-Ali, (Malaysian Society of Applied Biology, 2015)
Molecular markers represent an important tool for marker-assisted breeding in major crop plant breeding programmes. Applying molecular genetics to underutilised and minor crop species is more challenging as the funds available to research and develop such crops are often severely limited. Bambara groundnut is an underutilised African legume crop with good drought tolerance. It is also grown at low levels in Southeast Asia. In this review we examine some of the applications of DNA markers and illustrate their value in bambara groundnut.